ANALISIS ELASTISITAS DARI FUNGSI PENAWARAN IKAN NILA (Oreochromis niloticus) DI DESA BANGUNREJO KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA (STUDI KASUS DANAU GALIAN TAMBANG) - Agni Windi Kusuma Hastuti; Nurul Ovia Oktawati; Muhammad Syafril (2339-1324, 2018)
This study aimed to determine the level of price elasticity of supply function and the influence of price factors and production costs on the supply level of Nile oreochromis in Bangunrejo Village Tenggarong Seberang Subdistrict of Kutai Kartanegara Regency (Excavated Mine Lake). The data were collected by using census method with bid elasticity analysis and multiple linear regression analysis to determine the effect of price factor (